2020
DOI: 10.1002/aah.10100
|View full text |Cite
|
Sign up to set email alerts
|

Serum Protein Analysis of Nurse Sharks

Abstract: Serum protein electrophoresis (EPH) is used to assess relative concentrations of blood proteins in clinical and biological studies. Serum EPH fractions have been determined for elasmobranchs using mammalian albumin, alpha 1‐, alpha 2‐, beta‐, and gamma‐globulin fractions, and have been deemed fractions 1 through 5, respectively. However, serum EPH fraction concentration reference intervals (RIs) have not been widely established for different elasmobranch species. In this study, RIs for fractions 1 through 5 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…141 Agarose gel electrophoresis has also been used to describe the plasma proteins of other species, including the Atlantic sharpnose, spiny dogfish, bamboo, and nurse sharks. [142][143][144] The diversity in the protein electrophoretogram is reflected by the spotted eagle ray and bamboo shark (Figure 7). While an albumin migrating fraction is apparent in the ray, the same fraction represents <5% of the plasma protein in the shark species.…”
Section: El a S Mob R An Ch S Pecie Smentioning
confidence: 99%
“…141 Agarose gel electrophoresis has also been used to describe the plasma proteins of other species, including the Atlantic sharpnose, spiny dogfish, bamboo, and nurse sharks. [142][143][144] The diversity in the protein electrophoretogram is reflected by the spotted eagle ray and bamboo shark (Figure 7). While an albumin migrating fraction is apparent in the ray, the same fraction represents <5% of the plasma protein in the shark species.…”
Section: El a S Mob R An Ch S Pecie Smentioning
confidence: 99%
“…Despite its abundance, G. cirratum is listed as "Data Deficient" by the International Union for the Conservation of Nature (IUCN) due to a lack of information on its population dynamics and connectivity (Rosa et al, 2006). The body condition and some plasma metabolites of G. cirratum have been measured in prior research (i.e., AtallahBenson et al, 2020;Gallagher et al, 2017a;, however, intra-annual and intraspecific variation within this population has yet to be explored. Moreover, measures of ketone bodies in this species have not been assessed, despite their importance to elasmobranch energetics.…”
mentioning
confidence: 99%
“…Our PPE study revealed low quantities of proteins migrating in the pre-albumin region of the electrophoretogram for undulate skates (median 0.44% and 0.13 g/l) and nursehounds (median 0.64% and 0.17 g/l), which may contain high-density proteins as described in other elasmobranchs, and which we characterized as “Fraction 1” following the classification established in previous PPE studies with elasmobranchs in an effort to standardize electrophoretogram fractions for these species [ 3 , 22 ]. Low percentages and concentrations for fraction 1 agree with previous PPE studies with elasmobranchs which also reported similar values for this fraction: 1.30% and0.30 g/l in the Atlantic sharpnose shark, 0.71% and0.20 g/l in the bonnethead shark [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Samples were selected to form part of the RI after the detailed evaluation of every animal’s medical history and the completion of physical examinations (which included a hematological and biochemical analysis) to evaluate the condition of each individual sampled. For this study, we divided the electrophoretogram into several fractions following the guidelines established in previous studies with elasmobranchs, which already defined five different fractions in ray and shark species [ 3 , 4 , 9 , 22 , 23 ]. Caution was taken to delete the injection peak and the end delimiter produced by the urine buffer before electrophoretogram interpretation and division into fractions for its analysis.…”
Section: Methodsmentioning
confidence: 99%